콩 발아 중 isoflavone malonylglucosides의 함량 변이 - 이주원; Ju-won Lee; 이유정; Yoo-jung Yi; 이주희; Ju-hee Lee; 조민식; Min-sik Jo; 최도진; Do-jin Choi; 마무현; Mu-hyun Ma; et al. (Korean journal of crop science, 2018)
Soybean produces three major types of isoflavones, daidzein, genistein, and glycitein aglycones and their glucosides and malonylglucosides. It has been known that malonylated glucosides are rapidly converted to their corresponding aglycones due to the unstable thermolabile glucoside malonates; therefore, the analytical study of malonylated glucosides has been insufficient. In this study, we analyzed the malonylglucoside content in soybean seeds. Isoflavone analysis of three soybean cultivars revealed that 81.5~90.0% of the total isoflavones were malonylglucosides, whereas aglycones were rarely detected. Moreover, the total isoflavone content increased during a 5-day germination period where growth regulators and coumaric acid treatments tended to yield higher isoflavone content than the normal germination treatment, however the differences were not significant; notably, the isoflavone accumulation trend continued with additional germination days. The content of malonylglucoside was higher than that of other isoflavones, which was 83.7~86.6% of the total isoflavone content in seeds with a 3-day germination period. Furthermore, isoflavones were significantly accumulated in the hypocotyl of seedlings with a 5-day germination period. The content of isoflavone in the hypocotyl of the Pungsannamul-kong was 10,240 ug/g when treated with coumaric acid, which was considerably higher than that of other cultivars and treatments. Additionally, soybean seeds heated at 60℃ for 1 hour produced higher isoflavone content than non-heated soybean seeds. Our results show that it is possible to increase the isoflavone content in soybean seeds through various treatments.